COMMUNITY EMPOWERMENT: AN EMPOWERMENT EFFORT TOWARD YOUTH AT RISK - Widi, Muhammad Naufal; Yanti, Fitri; Faizal, Faizal (Universitas Islam Negeri Raden Intan Lampung, 2023)
Many teenagers carry out dangerous attitudes that interfere with their growth and development such as free sex, smoking, getting drunk, and so on. Society, especially parents, has a responsibility in dealing with the attitudes of adolescents. But not all people have good knowledge personally, and interpersonally in providing support and reactions to deviant attitudes. The research methods used are qualitative and quantitative research methods. Information collection methods were used through interviews, observations, surveys, and focus group discussions, with several elements of society from adolescents at risk, parents in general, and community leaders. The results showed that community knowledge is still weak both personally and interpersonally. Therefore, an assessment of the need for socialization planning involving the community was conducted. Then jointly carry out the implementation of socialization for adolescents with counseling on children's rights, social and assertive skills, helping skills, the formation of Children's Forums, and optimization of Children's Reading Parks. For parents, socialization on child protection and good parenting is conducted. Organizational strengthening is seen in the development of a network with the Bandar Lampung City Family Learning Center. The evaluation showed an increase in the empowerment of adolescents, parents, and organizations